Relayout dengan Menggunakan BLOCPLAN Tool Analysis - Anugerah, Budi; Nasution, Andri (Jurnal Sistem Teknik Industri, 2020)
PT. Industri Nabati Lestari or PT. INL is a subsidiary of PTPN 3 and PTPN 4 which is engaged in CPO processing. But from each production cycle, every raw material needed by PT. INL is not only supplied by PTPN itself, but many suppliers take part in the supply of raw materials. The problem faced by the company now is the inefficient flow of material in the current company layout from loading raw materials to the final product shipping process. Therefore the first thing is to observe the flow material problems, one of which is rearrangement or relayout using the ARC-BLOCPLAN method